Associations of MIND and DI-GM dietary scores with depression, anxiety, and gut microbiota in patients with colon cancer: a cross-sectional study - Meng, Yaqin; Tian, Jing; Xiu Li, Xiu; Xu, Zhou (Frontiers in Nutrition, 2025)
BackgroundDietary patterns influence psychological health, systemic inflammation, and gut microbiota composition in colon cancer patients. This study evaluates the associations of the Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) score and the Dietary Index for Gut Microbiota (DI-GM) with psychological outcomes, inflammatory markers, gut microbiota diversity (Shannon index) and composition (Firmicutes/Bacteroidetes ratio), and tumor biomarkers in colon cancer patients.MethodsA cross-sectional study was conducted on 630 colon Cancer patients. Multivariate linear regression models adjusted for demographic, clinical, and dietary factors assessed associations of MIND and DI-GM scores with depression, anxiety (HADS), sleep quality (PSQI), quality of life (FACT-C), inflammatory markers (CRP, IL-6, fecal calprotectin), F/B ratio, and tumor biomarkers (CEA, CA19-9).ResultsHigher MIND and DI-GM scores were significantly associated with better psychological outcomes and reduced systemic inflammation. Each one-unit increase in the MIND score was associated with lower depression (β = −1.16, 95% CI: −2.24 to −0.08) and anxiety (β = −2.48, 95% CI: −4.01 to −0.95). Similarly, DI-GM was inversely associated with depression (β = −1.36, 95% CI: −1.53 to −1.20), anxiety, and inflammatory markers. Tumor biomarkers such as CA19-9 and CEA showed significant inverse associations with both scores, especially DI-GM (CA19-9: β = −3.11, 95% CI: −4.93 to −1.29; CEA: β = −0.38, 95% CI: −0.55 to −0.20). The F/B ratio partially mediated the relationship between dietary scores and psychological outcomes but not inflammatory markers.ConclusionAdherence to MIND and DI-GM dietary patterns is associated with better psychological outcomes, lower inflammation, and favorable gut microbiota in colon cancer patients. DI-GM may better capture diet–gut microbiota–inflammation links, highlighting diet as a target to improve patient well-being.